Outbreak of highly pathogenic avian influenza in Minnesota in 2015: lessons learned. (March 2017) - Fitzpatrick, Ann; Mor, Sunil K.; Thurn, Mary; Wiedenman, Elizabeth; Otterson, Tracy; Porter, Robert E.; Patnayak, Devi P.; Lauer, Dale C.; Voss, Shauna; Rossow, Stephanie; Collins, James E.; Goyal, Sagar M.
The incursion of highly pathogenic avian influenza (HPAI) into the United States during 2014 resulted in an unprecedented foreign animal disease (FAD) event; 232 outbreaks were reported from 21 states. The disease affected 49.6 million birds and resulted in economic losses of $950 million. Minnesota is the largest turkey-producing state, accounting for 18% of U.S. turkey production. Areas with concentrated numbers of turkeys in Minnesota were the epicenter of the outbreak. The first case was presumptively diagnosed in the last week of February 2015 at the Minnesota Veterinary Diagnostic Laboratory (MVDL) and confirmed as HPAI H5N2 at the National Veterinary Services Laboratories on March 4, 2015. A total of 110 farms were affected in Minnesota, and the MVDL tested >17, 000 samples from March to July 2015. Normal service was maintained to other clients of the laboratory during this major FAD event, but challenges were encountered with communications, staff burnout and fatigue, training requirements of volunteer technical staff, test kit validation, and management of specific pathogen–free egg requirements.